OPTICAL CHARACTERIZATION OF MINERAL DUST CONTENT IN SNOW AND ICE CORES WITH DIGITAL IN-LINE HOLOGRAPHY - RAVASIO, CLAUDIA (Università degli Studi di Milano, 2022)
Aerosols are ubiquitous in the troposphere and influence the global climate by changing the radiative properties of the atmosphere: directly, through the scattering and absorption of solar and terrestrial radiation, and indirectly acting as cloud condensation and ice nuclei formation. Although extensive research has been carried out on this topic, significant uncertainties still affect current estimates of this contribution on the Earth’s energy balance. In this work, I studied the effects of the particle shape on the optical parameters for the radiative transfer through the atmosphere. I present the results of the characterization of mineral dust and micrometric particles transported and subsequently deposited on the surface of glaciers, and in time brought deeper, layer after layer. To this end, digital microscopic holography has proven to be an excellent suite for distinguishing non-spherical particles, going beyond the common spherical approximation. From the interference between the trans-illuminating reference field and the diffracted light by the particles in the forward direction, the cross-sectional area and the extinction cross-section can be numerically retrieved, thus providing a multi-parametric single-particle approach. This work develops a formal description of the technique through the theory of image formation in holographic microscopy, reporting a suite of validation measurements with calibrated particles, and providing an overview of the experimental results from Antarctic and Alpine snow and ice cores. The analysis reveals a remarkable variability in the extinction cross-section of the particles depending on their shape, with a prevalence of non-spherical particles, which proves the importance of measuring morphological and optical properties simultaneously. I also observed a prevalence of fine particles (< 2 μm in size), with the occurrence of aggregates and some giant particles (> 10 μm in size), especially in Alpine snow cores. Currently, global and regional models assume dust ...